Isolation and characterization of compounds from Podocarpus henkelii (Podocarpaceae) with activity against bacterial, fungal and viral pathogens - McGaw, Lyndy Joy (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2011.